The TLR9 Ligand, CpG‐ODN, Induces Protection against Cerebral Ischemia/Reperfusion Injury via Activation of PI3K/Akt Signaling. Issue 2 (10th April 2014) - Lu, Chen; Ha, Tuanzhu; Wang, Xiaohui; Liu, Li; Zhang, Xia; Kimbrough, Erinmarie Olson; Sha, Zhanxin; Guan, Meijian; Schweitzer, John; Kalbfleisch, John; Williams, David; Li, Chuanfu
Abstract : Background: Toll‐like receptors (TLRs) have been shown to be involved in cerebral ischemia/reperfusion (I/R) injury. TLR9 is located in intracellular compartments and recognizes CpG‐DNA. This study examined the effect of CpG‐ODN on cerebral I/R injury. Methods and Results: C57BL/6 mice were treated with CpG‐ODN by i.p. injection 1 hour before the mice were subjected to cerebral ischemia (60 minutes) followed by reperfusion (24 hours). Scrambled‐ODN served as control‐ODN. Untreated mice, subjected to cerebral I/R, served as I/R control. The effect of inhibitory CpG‐ODN (iCpG‐ODN) on cerebral I/R injury was also examined. In addition, we examined the therapeutic effect of CpG‐ODN on cerebral I/R injury by administration of CpG‐ODN 15 minutes after cerebral ischemia. CpG‐ODN administration significantly decreased cerebral I/R‐induced infarct volume by 69.7% (6.4±1.80% vs 21.0±2.85%, P <0.05), improved neurological scores, and increased survival rate, when compared with the untreated I/R group. Therapeutic administration of CpG‐ODN also significantly reduced infarct volume by 44.7% (12.6±2.03% vs 22.8±2.54%, P <0.05) compared with untreated I/R mice. Neither control‐ODN, nor iCpG‐ODN altered I/R‐induced cerebral injury or neurological deficits. Nissl staining showed that CpG‐ODN treatment preserved neuronal morphology in the ischemic hippocampus. Immunoblot showed that CpG‐ODN administration increased Bcl‐2 levels by 41% and attenuated I/R‐increased levels of Bax and caspase‐3 activity in ischemic brain tissues. Importantly, CpG‐ODN treatment induced Akt and GSK‐3β phosphorylation in brain tissue and cultured microglial cells. PI3K inhibition with LY294002 abolished CpG‐ODN‐induced protection. Conclusion: CpG‐ODN significantly reduces cerebral I/R injury via a PI3K/Akt‐dependent mechanism. Our data also indicate that CpG‐ODN may be useful in the therapy of cerebral I/R injury.